An Unusual Gross Appearance of Vulval Tuberculosis Masquerading as Tumor - Surekha U. Arakeri; Prachi Sinkar (Hindawi Limited, 2014)
Tuberculosis of the vulva is very rare. It is found in about 0.2% of the cases of genital tract tuberculosis. It usually presents as small shallow ulcers and multiple sinus tracts or rarely as elephantiasis of vulva. Except for very rare cases of primary tuberculosis in the vulva, it is usually associated with tuberculosis elsewhere in the body leading to secondary tuberculosis. Here, we report a case of secondary vulval tuberculosis which presented as a vulval mass in a 40-year-old female patient. The rarity of this presentation in the female genital tract is emphasized.